2022
DOI: 10.3390/biom12111706
|View full text |Cite
|
Sign up to set email alerts
|

E-Cadherin Expression Distinguishes Mouse from Human Hematopoiesis in the Basophil and Erythroid Lineages

Abstract: E-cadherin is a key regulator of epithelial cell–cell adhesion, the loss of which accelerates tumor growth and invasion. E-cadherin is also expressed in hematopoietic cells as well as epithelia. The function of hematopoietic E-cadherin is, however, mostly elusive. In this study, we explored the validity of mouse models to functionally investigate the role of hematopoietic E-cadherin in human hematopoiesis. We generated a hematopoietic-specific E-cadherin knockout mouse model. In mice, hematopoietic E-cadherin … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 68 publications
0
2
0
Order By: Relevance
“…The link between E-cadherin and hematopoiesis has been demonstrated in erythroid progenitors and it has been shown that E-cadherin has an erythroid lineage-restricted expression in BM cells and is involved in the maturation of erythroid progenitors [78]. Consistent with this, it was shown that E-cadherin is predominantly expressed in the basophil/mast cell lineage in mouse BM and that inhibition of E-cadherin causes a disruption of erythroid differentiation [78][79][80]. However, E-cadherin does not seem to be expressed in human basophils [79].…”
Section: E-cadherin In Acute Leukemiamentioning
confidence: 72%
See 1 more Smart Citation
“…The link between E-cadherin and hematopoiesis has been demonstrated in erythroid progenitors and it has been shown that E-cadherin has an erythroid lineage-restricted expression in BM cells and is involved in the maturation of erythroid progenitors [78]. Consistent with this, it was shown that E-cadherin is predominantly expressed in the basophil/mast cell lineage in mouse BM and that inhibition of E-cadherin causes a disruption of erythroid differentiation [78][79][80]. However, E-cadherin does not seem to be expressed in human basophils [79].…”
Section: E-cadherin In Acute Leukemiamentioning
confidence: 72%
“…Consistent with this, it was shown that E-cadherin is predominantly expressed in the basophil/mast cell lineage in mouse BM and that inhibition of E-cadherin causes a disruption of erythroid differentiation [78][79][80]. However, E-cadherin does not seem to be expressed in human basophils [79]. Although it is not easy to explain this phenomenon based on the existing literature, it can be envisioned as being a result of the evolutionary process.…”
Section: E-cadherin In Acute Leukemiamentioning
confidence: 84%